Biochemical and rheological properties of waxy wheat flour dough - Arrieta-Martinez, Melania (Kansas State University, 2016)
The rheological properties of two waxy and two normal wheat flours were investigated and the observed differences between them were explained by biochemical analysis. Protein analysis showed that waxy flour had lower polymeric to monomeric ratio (0.70 and 0.58 for waxy flour compared to 0.75 and 0.76 for normal flour) and higher gliadin content in waxy wheat dough (43.9 and 47.3 for waxy wheat dough compared to 41.0 and 41.7 for normal wheat dough). Waxy flour had high amounts of insoluble (IPP) and unextractable (UPP) polymeric protein despite the poor dough forming properties of the waxy flours, contrary to previous correlations made between IPP, UPP and dough strength. Gluten index determination showed a clear difference between waxy and normal flour; there was no gluten aggregation when the waxy samples were tested. The determination of gluten index done on a variety of water washed flour samples indicated that the water-extractable fraction may contain compounds that affect gluten aggregation. HPLC analysis coupled with arabinose/xylose ratio and viscosity determination of the water extractable portion of the flour indicated that water extractable arabinoxylans (WEAX) in waxy wheat flour were different in composition and conformation. Further research is needed to determine if they could be responsible for the lack of gluten aggregation in waxy flour.
Keywords: dough; wheat flour; rheological propertieswaxy